Pharmacogenetics of antipsychotic-induced metabolic disturbances: state-of-the-art - R. F. Nasyrova; N. A. Sivakova; D. V. Ivashchenko; D. N. Sosin; E. E. Ershov; K. A. Sosina; L. Sh. Akhmetova; O. V. Volikova; T. Z. Beybalayeva; N. G. Neznanov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Antipsychotics are the main pharmaceutical agents in treatment of schizophrenia and other mental disorders. According to literature data up to 60% of patients with schizophrenia have antipsychotic-induced metabolic disturbances. The main objective of pharmacogenetic studies is search for predictors of the response to therapy and definition of likelihood of development of undesirable phenomena. The main findings in the field of pharmacogenetics of metabolic disturbances were analysed. Recently, significant progress in the field of pharmacogenetic research was made which confirmed results of the previous studies and revealed new candidate genes. Ambiguous results in pharmacogenetic studies may be a reflection of complexity of pathogenesis of antipsychotic-induced weight gain, an influence of a set of epigenetic factors on mechanisms of its development. All this complicates design of the studies directed at identification of the candidate genes participating in realization of metabolic disturbances during intake of neuroleptics. Improvement of pharmacogenetic studies will provide the best understanding of how these genes are associated with antipsychotic-induced metabolic disturbances. Inclusion of pharmacogenetic approach in clinical guidelines is necessary, but now it is complicated that is associated mainly with the insufficient level of validity of the genetic markers studied and their ethnic heterogeneity. Use of pharmacogenetic testing improves rational therapy and contributes to the most efficient and safe therapy.